Pengaruh Ikatan Relasional dan Kepercayaan terhadap Niat Beli Ulang pada Shopee Live (Effect of Relational Bonds and Trust on Repurchase Intention in Shopee Live) - Rafiqatul hikmah (STIE Malangkucecwara, 2026)
This study aims to analyze the influence of relational bonds—including financial, social, and structural bonds—as well as consumer trust on repurchase intention among Shopee livestreaming users. A quantitative approach was employed using a survey method involving 200 respondents. The data were analyzed using PLS-SEM. The results indicate that structural bonds have a significant effect on trust in the host, while financial and social bonds do not show a significant effect. Trust in the host significantly influences trust in the product but does not directly impact repurchase intention. These findings suggest that consumer trust—particularly trust in the product—is a key factor in driving repurchase behavior, influenced by structural aspects and trust in the host.